Analysis of Prabowo's Speech in the Dynamics of the 12 Percent VAT Policy - Ayyubi Kholid Saifullah; Nani Nurani Muskin (CV. Publikasi Indonesia, 2025)
The 12 percent Value Added Tax (VAT) policy announced by President Prabowo in his speech on December 31, 2024, represents a strategic issue reflecting the government’s commitment to fostering economic justice. This study aims to analyze the deliberative rhetoric employed by President Prabowo to rationalize the VAT policy, particularly regarding its alignment with the interests of the lower-income population. The research utilizes a qualitative scientific approach (Moleong, 2021), with Aristotle’s rhetorical theory as the analytical framework. Deliberative rhetoric, which focuses on future-oriented persuasion to encourage specific actions or avoid them, is applied to understand the communication strategies used in the speech. The findings reveal that President Prabowo effectively integrates the rhetorical elements of ethos, pathos, and logos to build public trust, mitigate resistance, and promote an equitable policy. The VAT policy is targeted at luxury goods and services, while essential goods remain tax-free. This approach underscores the government’s prioritization of the lower-income population and its positive impact on income redistribution through fiscal policy. Further analysis demonstrates that the deliberative rhetoric used has the potential to create positive public perceptions of the policy, provided its implementation is consistent and transparent. This study contributes to the discourse on political rhetoric and fiscal policy by highlighting the importance of strategic communication in garnering public support for government initiatives